2004
DOI: 10.1023/b:apcs.0000018144.87456.10
|View full text |Cite
|
Sign up to set email alerts
|

One Setting for All: Metric, Topology, Uniformity, Approach Structure

Abstract: Abstract. For a complete lattice V which, as a category, is monoidal closed, and for a suitable Set-monad T we consider (T, V)-algebras and introduce (T, V)-proalgebras, in generalization of Lawvere's presentation of metric spaces and Barr's presentation of topological spaces. In this laxalgebraic setting, uniform spaces appear as proalgebras. Since the corresponding categories behave functorially both in T and in V, one establishes a network of functors at the general level which describe the basic connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 13 publications
1
52
0
Order By: Relevance
“…first group happen to be presentable as categories of lax algebras, that is: They are of the form Alg(T, V ), for a suitable extension T of a Set-monad T 0 = (T 0 , e, m) and a complete lattice V that comes with an associative and commutative binary operation ⊗ preserving suprema in each variable, and a ⊗-neutral element k (distinct from the bottom element ⊥), [5]. In this note, we show that this observation is not coincidental, that is: Coproducts in Alg(T, V ) are always stable under pullback, making Alg(T, V ) in fact an (infinitely) extensive category, provided that T 0 preserves inverse images.…”
mentioning
confidence: 99%
“…first group happen to be presentable as categories of lax algebras, that is: They are of the form Alg(T, V ), for a suitable extension T of a Set-monad T 0 = (T 0 , e, m) and a complete lattice V that comes with an associative and commutative binary operation ⊗ preserving suprema in each variable, and a ⊗-neutral element k (distinct from the bottom element ⊥), [5]. In this note, we show that this observation is not coincidental, that is: Coproducts in Alg(T, V ) are always stable under pullback, making Alg(T, V ) in fact an (infinitely) extensive category, provided that T 0 preserves inverse images.…”
mentioning
confidence: 99%
“…Since one part of "⇒" has already been considered in, e.g., [4], we show thatŤ =T ϕ . Given a W -relation X s / / Y , on the one hand, compatibility of ϕ givesT (ϕ s) ϕ (Ť s), and thus, ϕT (ϕ s) Ť s by Definition 2.13; on the other hand,Ť s…”
Section: From Nuclei To Quotientsmentioning
confidence: 85%
“…This section briefly outlines the setting of lax-algebraic approach to topology as it is developed in, e.g., [4,7,12,13,24]. The theory was motivated by the result of M. Barr [2], who showed that the category Top of topological spaces and continuous maps is isomorphic to the category of lax Eilenberg-Moore algebras with respect to the canonical lax extension of the ultrafilter monad on the category Set of sets and maps to the category Rel of sets and relations.…”
Section: (T V )-Categories and (T V )-Functorsmentioning
confidence: 99%
See 2 more Smart Citations